Preleukaemic clonal haemopoiesis and risk of therapy-related myeloid neoplasms: a case-control study. Issue 1 (January 2017) - Takahashi, Koichi; Wang, Feng; Kantarjian, Hagop; Doss, Denaha; Khanna, Kanhav; Thompson, Erika; Zhao, Li; Patel, Keyur; Neelapu, Sattva; Gumbs, Curtis; Bueso-Ramos, Carlos; DiNardo, Courtney D; et al.
Summary: Background: Therapy-related myeloid neoplasms are secondary malignancies that are often fatal, but their risk factors are not well understood. Evidence suggests that individuals with clonal haemopoiesis have increased risk of developing haematological malignancies. We aimed to identify whether patients with cancer who have clonal haemopoiesis are at an increased risk of developing therapy-related myeloid neoplasms. Methods: We did this retrospective case-control study to compare the prevalence of clonal haemopoiesis between patients treated for cancer who later developed therapy-related myeloid neoplasms (cases) and patients who did not develop these neoplasms (controls). All patients in both case and control groups were treated at MD Anderson Cancer Center (Houston, TX, USA) from 1997 to 2015. We used the institutional medical database to locate these patients. Patients were included as cases if they were treated for a primary cancer, subsequently developed therapy-related myeloid neoplasms, and had available paired samples of bone marrow from the time of therapy-related myeloid neoplasm diagnosis and peripheral blood from the time of primary cancer diagnosis. Patients were eligible for inclusion as age-matched controls if they were treated for lymphoma, received combination chemotherapy, and did not develop therapy-related myeloid neoplasms after at least 5 years of follow-up. We used molecular barcode sequencing of 32 genes on the pretreatment peripheral blood samples to detect clonal haemopoiesis. For cases, we also used targeted gene sequencing on bone marrow samples and investigated clonal evolution from clonal haemopoiesis to the development of therapy-related myeloid neoplasms. To further clarify the association between clonal haemopoiesis and therapy-related myeloid neoplasm development, we also analysed the prevalence of clonal haemopoiesis in an external cohort of patients with lymphoma who were treated in a randomised trial of front-line chemotherapy with cyclophosphamide, doxorubicin, vincristine, and prednisone, with or without melatonin. This trial was done at MD Anderson Cancer Center between 1999 and 2001 (protocol number 98-009). Findings: We identified 14 cases and 54 controls. Of the 14 cases, we detected clonal haemopoiesis in the peripheral blood samples of ten (71%) patients. We detected clonal haemopoiesis in 17 (31%) of the 54 controls. The cumulative incidence of therapy-related myeloid neoplasms in both cases and controls at 5 years was significantly higher in patients with clonal haemopoiesis (30%, 95% CI 16–51) than in those without (7%, 2–21; p=0·016). In the external cohort, five (7%) of 74 patients developed therapy-related myeloid neoplasms, of whom four (80%) had clonal haemopoiesis; 11 (16%) of 69 patients who did not develop therapy-related myeloid neoplasms had clonal haemopoiesis. In the external cohort, the cumulative incidence of therapy-related myeloid neoplasms at 10 years was significantly higher in patients with clonal haemopoiesis (29%, 95% CI 8–53) than in those without (0%, 0–0; p=0·0009). In a multivariate Fine and Gray model based on the external cohort, the presence of clonal haemopoiesis significantly increased the risk of therapy-related myeloid neoplasm development (hazard ratio 13·7, 95% CI 1·7–108·7; p=0·013). Interpretation: Preleukaemic clonal haemopoiesis is common in patients with therapy-related myeloid neoplasms at the time of their primary cancer diagnosis and before they have been exposed to treatment. Our results suggest that clonal haemopoiesis could be used as a predictive marker to identify patients with cancer who are at risk of developing therapy-related myeloid neoplasms. A prospective trial to validate this concept is warranted. Funding: Cancer Prevention Research Institute of Texas, Red and Charline McCombs Institute for the Early Detection and Treatment of Cancer, NIH through MD Anderson Cancer Center Support Grant, and the MD Anderson MDS & AML Moon Shots Program.